Augmented Reality for 3D Geometric Shapes and Nets Combination for Android - Wulansari, Ossy Dwi Endah; Zaini, Teuku Muhammad; Bachry, Bobby; Nursiyanto, Nursiyanto (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
Nets of 3D geometric shapes are flat patterns that can be folded into 3D objects when their edges are joined. Comprehending these nets is essential, but it can be challenging because they are generally presented only as 2D images in textbooks, making them difficult to visualize without physical models. Augmented reality (AR) provides an interactive approach to visualizing 3D shapes more effectively. This study aims to develop an Android app named AR 3DNETS, which utilizes a paper cone as a 3D object marker, allowing students to interact with 3D models using their smartphones. The research follows the Multimedia Development Life Cycle (MDLC) approach, encompassing concept development, design, material collection, assembly, testing, and distribution stages. Testing results indicate that AR 3DNETS functions properly, with all buttons working correctly and compatibility across Android versions 9.0 to 13.0. The results of the data obtained from the survey indicate that the AR 3DNETS application got 17 markers with a really great category, and 3 pointers with a great category. The results of the survey suggest that learning with the AR 3DNETS application is doable to be utilized as a learning media for nets of 3D shapes. Separated from that, the evaluation criteria which talk about fun, curiosity, and simple to utilize focuses, received a rate of 82.58%, 84.52%, and 85.81%, these rates are included within the